The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.8100
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative CT for Neuronavigation Guidance and Confirmation of Foramen Ovale Cannulation for Glycerol Trigeminal Rhizotomy: A Technical Report and Case Series

Abstract: Glycerol rhizotomy was originally described as an initial surgical treatment for trigeminal neuralgia after the failure of medical therapy. Here we describe its use as a salvage procedure, typically after failure of multiple other modalities including microvascular decompression, stereotactic radiosurgery, and/or other percutaneous procedures. Foramen ovale cannulation as a "salvage procedure" may be complicated by lack of cerebrospinal fluid (CSF) return despite adequate cannulation of the foramen ovale, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…4 Given its technical challenge and lack of CSF return in some cases, making the conventional fluoroscopic confirmation of adequate cannulation less certain, some studies have proposed salvage procedures using CT-and MRI-guided navigation and frameless navigation to overcome these challenges for accurate cannulation of the foramen ovale and Meckel's cave with improving outcomes. [21][22][23] Minimally invasive procedures and approaches have been used to treat various neurosurgical diseases. 9 Over the past decade, endoscopic approaches have gained popularity and have been used for spinal, transcranial, and skull base approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Given its technical challenge and lack of CSF return in some cases, making the conventional fluoroscopic confirmation of adequate cannulation less certain, some studies have proposed salvage procedures using CT-and MRI-guided navigation and frameless navigation to overcome these challenges for accurate cannulation of the foramen ovale and Meckel's cave with improving outcomes. [21][22][23] Minimally invasive procedures and approaches have been used to treat various neurosurgical diseases. 9 Over the past decade, endoscopic approaches have gained popularity and have been used for spinal, transcranial, and skull base approaches.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Given its technical challenge and lack of CSF return in some cases, making the conventional fluoroscopic confirmation of adequate cannulation less certain, some studies have proposed salvage procedures using CT- and MRI-guided navigation and frameless navigation to overcome these challenges for accurate cannulation of the foramen ovale and Meckel's cave with improving outcomes. 21 22 23 …”
Section: Discussionmentioning
confidence: 99%
“…These new features in the procedure of RF rhizotomy of the gasserian ganglion have concerned facilitation of cannulation of the foramen ovale. More recently, another major improvement in the technique has emerged and aimed at placing the tip of the electrode at an optimal area inside the Meckel's cave (Thatikunta et al, 2020; Tsai et al, 2019). For this, a stereotactic planning system and a combination of preoperative MRI and intraoperative CT were used to provide visualization of the electrode into the Meckel's cave.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of RF thermocoagulation is usually performed under the guidance of fluoroscopy. More recently, some reports have been published on the use of computed tomographic or navigation guidance, or both (Arishima et al, 2016; Easwer et al, 2016; Lin et al, 2011; Thatikunta et al, 2020; Tsai et al, 2019; Weßling & Duda, 2019; Yang et al, 2010). These new systems can facilitate cannulation of the foramen ovale, especially for less experienced surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies showed the utility of 3-dimensional (3-D) intraoperative computerized tomography (CT)-based or MRI-based neuronavigation in improving the accuracy of needle localization and trajectory. [4][5][6][7][8] The purpose of this study was to assess the benefit of incorporating 3-D augmented reality (AR) into the planning and performance of these percutaneous procedures. AR overlays virtual content on the real world and therefore has the potential to improve localization of surgical targets that are unexposed to the human eye.…”
mentioning
confidence: 99%